Theoretical Framework Pemikiran Mulla Sadra dan Aktualisasinya dalam Pendidikan Islam - Muhammad Umar Hasibullah (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2023)
The relationship between science and religion, both in the ontological, epistemological and axiological realms, always leaves problems that are never finished being discussed. Science today is being dictated due to the western secularization movement so that there is a separation between general science and religious science. General science is identified with science whose source is taken from the universe, while religious science is derived from revelation, even though all of it comes from the same source, namely God Almighty because revelation and the universe are all verses of Allah, so if you look at the development of science in Islam, there is no dichotomy between religious science and non-religious science. This research uses qualitative research methods with a descriptive type of research. The techniques used in data collection in this study used literature study techniques. Literature Study is a data collection technique by searching and studying various data, articles, document archives, and literature books as well as previous research that is considered relevant. In this study, Literature Studies were carried out by collecting library materials obtained from various literature such as books, scientific journals, previous research, news in the media. The unity of science and religion is at the level of the world of Intellection which is absolute truth. At this level science and religion are in existential unity, because both are within and part of God. Thus, in essence in the context of the unity of Wujūd , there is no dichotomy between the science of God and the science of human creation, since that dichotomy would presuppose that there is a science of human creation that seems to be outside the science of God. The distinction between naqliyah (derived from revelation) and aqliyah (derived from reason) does not indicate that naqliyah science is God's science while aqliyah is human science. But the concepts of naqliyah and aqliyah are epistemological concepts of the way in which man discovers the truth. As for the science itself in the form of qauliyah verses and kauniyah verses, both are the knowledge of Allah. Man has no knowledge but masters knowledge (because God has the power to deprive man of the knowledge). Also, it is appropriate to say that man is not the creator of science but the inventor of science.